Understanding resilience in adolescents: the relationship between stress, resources and well-being - Azlin binti Hj Alwi (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
The present study was carried out to understand the relationship between stressors, resilience resources and well-being in adolescents. Two sets of studies were carried out to achieve this. In the first study, the objectives were (i) to examine possible factors at the individual and socio-environmental levels that distinguish between resilient and non-resilient adolescents, and (ii) to examine the role of resilience resources on the stressor - well-being relationship. Based on the results of Study 1, the second study aimed to test the effectiveness of resilience-based intervention in improving adolescents' perceived social support, life satisfaction, and distress. In Study 1, the sample consisted of 294 adolescents aged 12-19 years (mean=15.19, sd=2.38). Results of the k-mean clustering technique identified 30.0% of the adolescents as resilient (high stress, high well-being) and 28.6% as maladjusted (high stress, low well-being). Resilient adolescents were found to have significantly higher scores on all the resilience resources (religious strength, personality, guardian-child communication style, social support, and school coherence) compared to the non-resilient maladjusted group. In addition, results of the structural equation modeling analysis indicated that resilience resources acted as a mediator in the relationship between stressors and well-being. In Study 2, the effectiveness of resilience-based intervention was examined by dividing 33 participants into two groups: the control group (n= 17) and the treatment group (n= 16). These two groups completed pre- and posttest scores on three measures: ( 1) Multidimensional Scale of Perceived Social Support (MSPSS; Zimet, Dahlem, Zimet, & Farley, 1988); (2) The Brief Multidimensional Students' Life Satisfaction Scale (BMSLSS; Valois, Zullig, Huebner, & Drane, 2004); and (3) GHQ12 (Goldberg & Williams, 1988). Results showed that those in the treatment group reported higher social support, while no significant difference was shown in their life satisfaction and distress scores. Results of both studies have important implication for all counselors, teachers, and social workers who operate in school settings. The findings can be used to develop comprehensive school guidance plans, specifically when planning small group interventions. These findings were further discussed with respect to the current literature on stressors, resilience resources, and well-being.